Image-Guided Spine Interventions - Mathis, John M.; Golovac, Stanley; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
As image-guided spine interventions have increasingly become a primary strategy for managing back pain, the tools and capabilities available to practitioners have grown significantly. This fully revised edition of Image-Guided Spine Interventions presents the latest procedures available to physicians who perform minimally invasive spine interventions. The comprehensive text covers the fundamentals$1 (Bsuch as spine anatomy, procedural materials, and pharmacological requirements$1 (Balong with chapters devoted to key topics such as discography, percutaneous descectomy, vertebroplasty and balloon kyphoplasty, epidural steroid injections, and autonomic nerve blocks. Additionally, three new chapters are included in the Second Edition, covering pulsed radiofrequency procedures, sacroplasty, and spinal cord stimulation. Each technique is presented in a straightforward manner that allows the reader to effectively evaluate and implement new procedures. The text is further enhanced by nearly 200 images and illustrations. Edited by Dr. John Mathis, a former president of the American Society of Spine Radiology, and Dr. Stanley Golovac, who both have clinical practices devoted solely to spine procedures and pain management, the book will be useful to all physicians dealing with back pain, including radiologists, pain anesthesiologists, spine neurosurgeons, and orthopedists. Physicians will once again find that Image-Guided Spine Interventions, 2nd Edition, is the pivotal authority on image-guided techniques for the spine.s
Spine Anatomy -- Materials Used in Image-Guided Spine Interventions -- Patient Evaluation and Criteria for Procedure Selection -- The Surgeon$1 (Bs Perspective: Image-Guided Therapy and Its Relationship to Conventional Surgical Management -- Image-Guided Percutaneous Spine Biopsy -- Discography -- Percutaneous Lumbar Discectomy -- Epidural Injections for the Treatment of Spine-Related Pain Syndromes -- Pulsed Radiofrequency Procedures in Clinical Practice -- Facet Joint Injections and Sacroiliac Joint Injections -- Autonomic Nerve Blockade -- Percutaneous Vertebroplasty -- Implanted Drug Delivery Systems -- Endovascular Treatment of Vascular and Nonvascular Diseases of the Spine -- Kyphoplasty: Balloon Assisted Vertebroplasty -- Sacroplasty -- Spinal Cord Stimulation: Uses and Applications.s
Keywords: Medicine; Anesthesiology; Radiology, Medical; Interventional radiology; Neurosurgery; Orthopedics; Pain Medicine; Medicine & Public Health; Imaging / Radiology; Anesthesiology; Interventional Radiology; Neurosurgery; Orthopedics; Pain Medicine